The Role of Brand Image in Mediating Celebrity Endorser Credibility and E-Wom on Repurchase Intention (Study on Avoskin Consumers in Denpasar) - I Gusti Ayu Uthami Febriati; I Wayan Santika; I Made Wardana; Ni Ketut Seminari (Return : Study of Management, Economic and Bussines, 2025)
The Theory of Planned Behavior (TPB) and the Stimulus-Organism-Response (SOR) model are theoretical frameworks that explain how external stimuli, such as celebrity endorser credibility and electronic word of mouth (E-WOM), are psychologically processed by individuals, ultimately leading to specific behavioral intentions. In the highly competitive skincare industry, Avoskin is ranked among the top five skincare brands but experienced a decline in sales in 2022, making the enhancement of consumers’ repurchase intentions a crucial focus for the company. This study aims to analyze the influence of celebrity endorser credibility and E-WOM on the repurchase intention of Avoskin products, with brand image as a mediating variable. The research was conducted among residents of Denpasar City who had previously purchased Avoskin products, using purposive sampling with a total of 150 respondents. Data were collected through an online questionnaire and analyzed using Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach. The results indicate that both celebrity endorser credibility and E-WOM have a positive and significant effect on repurchase intention. Additionally, both variables positively and significantly influence brand image. Brand image, in turn, has a significant effect on repurchase intention and serves as a mediating variable in the relationship between celebrity endorser credibility and E-WOM with repurchase intention. The study suggests that companies should select credible public figures who align with the brand image and encourage positive online reviews. Moreover, companies are advised to highlight product advantages such as natural active ingredients, dermatological certification, and eco-friendly packaging. Consumer experience-based loyalty strategies should also be enhanced. Future research is encouraged to include additional variables, such as brand trust or consumer satisfaction, to further enrich the conceptual model.